2020
DOI: 10.18551/rjoas.2020-02.18
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Type Characteristics and Seed Yield of Proso Millet (Panicum Miliaceum L.) Response to Plant Density

Abstract: Yield of proso millet was usually low due to chaotic planting density in arid and semi-arid areas of China. To get high yield in proso millet, planting density and plant-type characteristics were explored. This study was carried out in the field to determine the effects of planting density (30, 45, 60, 75 and 90×10 4 plants ha -1 ) on plant-type characteristics and yield components. With an increment in planting density, panicle length, grain weight per panicle, grain density, total grain, plant height, panic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The planting density was 55 plants m −2 , with a distance between rows of 60 cm and 3 cm between the plants in each row. The applied planting density was adopted based on recent studies [30] in order to optimize and standardize the experiment using an average density used in open field. Each experimental plot measured 2.4 m in length and 3 m in width (7.2 m 2 ), and was sown, as classically happen for spring crops in that area, at the beginning of May (4 May 2018 and 9 May 2019).…”
Section: Field Experimentsmentioning
confidence: 99%
“…The planting density was 55 plants m −2 , with a distance between rows of 60 cm and 3 cm between the plants in each row. The applied planting density was adopted based on recent studies [30] in order to optimize and standardize the experiment using an average density used in open field. Each experimental plot measured 2.4 m in length and 3 m in width (7.2 m 2 ), and was sown, as classically happen for spring crops in that area, at the beginning of May (4 May 2018 and 9 May 2019).…”
Section: Field Experimentsmentioning
confidence: 99%
“…However the recently published proso genome sequence and chromosome assembly in 2019 projected this species into the modern genomics era, disclosing a great potential for large-scale genotyping applications and, hence, future molecular-assisted breeding programs [23]. A few studies indicated that P. miliaceum crop performance was particularly affected by two management practices, nitrogen fertilization (N) and plant density (D), adopted during the growing cycle [24,25]. Nitrogen seems to be the major element required to boost the potential yield; studies revealed that the optimum range may vary between 50 and 150 N kg ha −1 , according to pedoclimatic conditions [17,26].…”
Section: Introductionmentioning
confidence: 99%